Successful Repair of Distal Aortic Arch and Proximal Descending Aortic Aneurysm with Coronary Artery Bypass Grafting- a case report. (Bangladesh Heart Journal, 2024)
Thoracic aortic aneurysm (TAA) is a rare condition causing dilatation of the thoracic aorta. TAA puts the individual at the risk of aortic dissection, aortic rupture and ultimate death. Diagnosis often requires good radiological support, whereas treatment requiring dedicated aortic program. In a third world country like us, with a population of 170 million or more, due to scarce facilities, surgeons are less interested to perform these types of surgeries. We hereby presenting a case of aortic aneurysm that involved distal aortic arch and proximal descending thoracic aorta (DTA) with significant double vessel coronary artery disease, who was successfully treated by our team.(Bangladesh Heart Journal 2024; 39(2): 172-176